2017
DOI: 10.24099/vet.arhiv.160719a
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of extended-spectrum cephalosporinase producing Escherichia coli in kuroiler birds

Abstract: the present study was undertaken to detect the incidence of extended-spectrum-cephalosporinase gene possessing-Escherichia coli, its co-resistance pattern against other antimicrobials, and the clonal relationship of the isolates in healthy kuroiler birds. a total of 80 cloacal swabs from kuroilers were collected randomly from West Bengal, India. the use of costly antimicrobials (cephalosporins) was not practiced by farmers. Escherichia coli was isolated and identified by standard biochemical tests and 16SrRNA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
2
1
Order By: Relevance
“…Among food animals that act as reservoirs of ESBLproducing E. coli, broilers were considered to be the most potent reservoir Pacholewicz et al (2015).In this study the percentage of blaTEM gene from the isolated E .coli strains was 100 % (10 out of 10 strains) which nearly go hand with the results of Maram (2014) who detected blaTEM gene in 18 out of 19 E.coli isolates with 94.73%. But these results disagreed with Ghosh et al (2017) who obtained lower percentage about 10%from isolated E. coli.…”
Section: Discussioncontrasting
confidence: 68%
“…Among food animals that act as reservoirs of ESBLproducing E. coli, broilers were considered to be the most potent reservoir Pacholewicz et al (2015).In this study the percentage of blaTEM gene from the isolated E .coli strains was 100 % (10 out of 10 strains) which nearly go hand with the results of Maram (2014) who detected blaTEM gene in 18 out of 19 E.coli isolates with 94.73%. But these results disagreed with Ghosh et al (2017) who obtained lower percentage about 10%from isolated E. coli.…”
Section: Discussioncontrasting
confidence: 68%
“…The mechanism of spread of antibiotic resistance from animals to humans and vice versa remains controversial. Studies have reported that E. coli which can be isolated from water, food and farm animals is associated with antimicrobial resistance [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…This investigation revealed that the studied birds harbour CTXC-M-producing Klebsiella spp. which might be transmitted to the food chain either directly or indirectly [13,14].…”
Section: Prevalence Of Antibiotic Resistant Bacteria In Studied Animamentioning
confidence: 99%